Dispersal and colonization success of ground beetles (Coleoptera, Carabidae) on the Solovetsky Islands (the largest archipelago of the White Sea) - Natalia A. Zubrii; Boris Yu. Filippov; Ivan N. Bolotov (Acta Biologica Sibirica)
In this study, we analyzed the patterns of dispersal and colonization of ground beetles on the Solovetsky Islands. Our goals were to: (1) revise the Carabidae fauna and its structure, including that of the nearby mainland Onega Peninsula; (2) explore the migration flow of species from the mainland; and (3) reveal the spatial and temporal structures of carabid communities on the Solovetsky Islands. We collected specimens of ground beetles during the summer months from 2008 to 2010 and in 2024 on the Solovetsky Archipelago and the Onega Peninsula (in the suburbs of Onega town) in 2011 and 2012. Using pitfall traps and hand-capture methods, we gathered 19,925 Carabidae specimens identified as 80 species on the Solovetsky Islands, while the Onega Peninsula yielded 1,696 specimens representing 85 species. Cluster analysis supported the biogeographic theory that the primary migration flow of Carabidae to the archipelago was from nearby mainland territories, particularly the Onega Peninsula. Both local faunas exhibited a high proportion (over 70%) of macropterous species; however, brachypterous species were more abundant on the islands. We did not find significant interannual changes in the species composition of the carabid fauna on the archipelago. Cluster analysis and non-metric multidimensional scaling (MDS) revealed that the carabid communities maintained stable spatial and temporal structures among studied sites. Carabid assemblages of natural vegetation types, such as forests and seaside meadows, were more stable than those of anthropogenic meadows. Carabid communities of forests showed the highest stability year-to-year (up to 74% according to the partial Mantel test).